Medical Culture and Inbreeding: A Field Study in Baghdad - زيـنب صالح وهاب, الباحثة (lark, 2021)
Family awareness of health safety is the basis on which societies are constructed. Women, in particular, play an important role in improving the health safety within their families through making conscious decisions and applying the most appropriate methods of dealing with that. Due to its significance in preventing hereditary disorders, premarital medical examinations are necessary to be done when inbreeding is intended. Inbreeding can result in issues on the health, social, economic, and psychological levels of the family, in turn on the society. The official institutions will be negatively affected by the aforementioned problems, and therefore will increase the health services and the financial costs. To achieve the objectives of the present study, the researcher used a social survey that involved (200) respondents from families, and (200) respondents from workers in the centers of genetic blood diseases in the Karkh and Rusafa, in Baghdad.
Keywords: Medical culture - inbreeding